2020
DOI: 10.36341/jomis.v4i2.1336
|View full text |Cite
|
Sign up to set email alerts
|

Strategi Edukasi Gizi Dan Efektivitas Media Poster Sebagai Implementasi Keluarga Sadar Gizi (Kadarzi)

Abstract: Lowness of the nutrition Awareness family (Kadarzi) percentage only 29,6%. Low birth weight about 104 cases on January until July of 2018 at the Arifin Achmad Regional Hospital. Facing the lack behavior in the in the healthy lifestyle as long as the pregnancy. This study aimed  to develop the poster media as the strategic education for the medical, maternal infant and Balita’s, then knowing effectivity of the poster media as the reach effort to Kadarzi at the Arifin Achmad Regional Hospital of Riau Province. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Another research was conducted by Andriani, Suwarni, & Arfan (2020) by using posters as an alternative media to wash hands. Wiji & Fitri (2020) and Andriani et al (2020) have something in common with this study, namely using poster media as a health promotion medium. The results also showed that posters were suitable for use as a health promotion medium.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another research was conducted by Andriani, Suwarni, & Arfan (2020) by using posters as an alternative media to wash hands. Wiji & Fitri (2020) and Andriani et al (2020) have something in common with this study, namely using poster media as a health promotion medium. The results also showed that posters were suitable for use as a health promotion medium.…”
Section: Discussionmentioning
confidence: 99%
“…The use of posters as a medium for health promotion had become the object of research that was often carried out in health. Wiji & Fitri (2020) using posters as a media strategy for nutrition education to increase knowledge of postpartum mothers, babies, and toddlers. Another research was conducted by Andriani, Suwarni, & Arfan (2020) by using posters as an alternative media to wash hands.…”
Section: Discussionmentioning
confidence: 99%